A comparative study of cooperation models in city council and municipalities with the health system in Iran and selected countries - Najmeh Khodadadi; Aidin Aryankhesal; Mohammadreza Maleki (Wolters Kluwer Medknow Publications, 2021)
AIM: This study aimed to identify models for the participation of the city council and municipality with the health system in selected countries. SUBJECTS AND METHODS: This is a descriptive comparative study conducted in 2020 qualitatively. The countries studied were examined in terms of the following characteristics: type of political structure, type of health system, level of cooperation between local government and health system, municipal financing, type of financial participation of local government and health system, method or institution for participation Created, level of participation, local government influence on health system decisions, advantages and disadvantages of a partnership between local government and health system. Data were collected through valid databases (PubMed, Scopus, Embase, and Google Search engine) and website of the World Health Organization, local government, and the Ministry of Health of countries concerned and analyzed in a framework of analysis. RESULTS: Countries were divided into two groups in terms of a partnership between the health system and local governments, which had a distinct partnership between the health system and local government and without their participation. Factors that contribute to the creating and strengthening of partnerships include beliefs of health authorities and local government, the need for participation, transparency in participatory programs, designing a specific mechanism for participation, local authority, and financing joint participation plans. CONCLUSION: In countries with planned participation, citizens have better access to services. Citizens' participation, as well as the private sector, is greater in health issues. In these countries, participation in health financing by the private sector and other related agencies has increased. Planning and service delivery increases according to neighborhood needs. The variety of services provided and the use of new methods of service are more, and in these countries, the focus of the Ministry of Health on the preparation of strategies and monitoring the quality of services is increasing.